Comparative Analysis of Energetic Performance of Various Photovoltaic Power Stations - Chalbash O.; Berzan V.; Postolati V. (Problems of the Regional Energetics, 2018)
Factors affecting the production of electricity by photovoltaic (PV) power plants are studied. It is worth noting that reducing the shade and orientation to the sun are effective solutions for an in-crease in the production of electricity by these PV plants. A brief overview of the features of stationary installations and installations in the tracking of the sun is presented. The purpose of the paper is to justify, develop, and describe a generalized approach to analyzing the operation and methods of tracking the sun by the platforms with photovoltaic modules so as to increase the specific energy density obtained from a given surface of the photovoltaic installation. A concept is formulated and the generalized mathematical model is developed for different photo-voltaic plants with fixed and mobile platforms, taking into account the shading effect of photo-voltaic modules mounted on different platforms. Based on the decomposition concept, the op-timization problem is solved on the criterion of the maximum value of the electric energy and the occupation of the smallest area of the site for a PV plants. A software for calculating the electricity produced by PV plants with stationary and mobile platforms was elaborated according to their location on the land meant for a certain PV plants. Specific electricity production kWh / (m2*day) indices were determined for different PV plants, taking into account the shading fac-tor. It was found that the PV plants equipped with three-coordinate orientation systems can pro-duce the largest amount of energy, in addition, providing higher energy performance indices compared to those of other types of PV plants.